Why do women with early breast cancer in Northern Sri Lanka undergo mastectomy? Decision-making and ways forward - Chrishanthi, R.; Kumar, R.; Dhivya, S.T.; Gopikha, S.; Muthulingam, S.; Vengadasalam, S. (Jaffna Medical Association, 2024)
Introduction: Despite robust evidence confirming equivalent survival rates and better cosmetic outcomes with breast-conserving surgery (BCS) and radiotherapy compared to mastectomy, the rates of mastectomy among women with early breast cancer have not declined significantly in Sri Lanka. Objective: This study explores views on the surgical treatment of early breast cancer among Northern Sri Lankan women who were eligible for BCS but underwent mastectomy. Methods: An exploratory descriptive qualitative study was carried out among 15 women who underwent mastectomy for early breast cancer. Patients who were referred to the Tellippalai Trail Cancer Hospital for adjuvant therapy after mastectomy and matched the study criteria were recruited. Data were collected through in-depth semi-structured interviews, which were transcribed in Tamil, translated into English, coded using QDA Miner Lite software, and analysed thematically. Results: Seven out of 15 participants were not aware of breast-conserving surgery (BCS) as a treatment option or their eligibility for BCS at the time of mastectomy. According to participant narratives, the treating team had recommended mastectomy to most participants. While most opted for mastectomy, believing that it was associated with lower rates of recurrence and spread compared to BCS, these beliefs were frequently reinforced by the treating team. The pros and cons of the two approaches had not been discussed before surgery with most participants and in the absence of information, family and friends weighed in on the decision to opt for mastectomy, ultimately resulting in feelings of loss and regret in most instances. Conclusion: Most participants were not aware that they were eligible for BCS. These information gaps need to be urgently addressed so that women can make informed decisions about their health.
Keywords: Breast-conserving surgery; Modified radical mastectomy; Shared decision making; Pre-surgical counselling; Sri Lanka